Leitura na escola: análise de um projeto literário - Damasceno, Ana Maria (2010)
The theme of this work is related to the teaching of literature in school, especially in high school. This study had as a general purpose to assess to what extent the Literary Project that has being developed at the State School Tarcísio Soares Palmeira, located in São Miguel dos Campos - AL. has contributed to the development of reading among his students. More specifically, this research was carried out in order to analyze and evaluate the literary project conducted in 2008, to determine whether this project has contributed to the literary consciousness of students through the assessment revealed by teachers and students of that school. The survey is a case study, in which the author counted on with the participation of 265 students and 9 teachers. The methodology used three instruments to collect data: observation of the context of the practice of the Literary Project; questionnaires answered by the students and teachers, as well as interviews that were carried out in order cross data about the informants’ opinions and expectations. The research involved quantitative data, document analysis, tabulation and analysis of results. The results showed that the Literary Project developed by that school was a positive teaching and learning experience of reading and has contributed significantly to the development of the literary awareness among the students involved in the project. However, it was verified that there are still some issues considered critical that need to be reflected by the school community, to improve the development process of future projects.